Ultrasound propagation in two-layer gas flow. (18th October 2019) - Taskin, Mahjabin; Kido, Takuya; Inoue, Masahiro; Kato, Yoshimine
Abstract: The ultrasonic signal propagation in two-layer gas flow was studied. The intensity degradation of the signal was observed while the signal was propagating through the air-hydrogen-air two-layer gas flowing system. The concentration of flowing hydrogen (H2 ) gas was measured using ultrasound from the exterior of the pipe, and it was calculated that the intensity degradation of signal did not simply depend on the H2 concentration, however, the intensity varied every second. Schlieren photography was taken to visualize the motion of H2 gas after injecting into the flowing air of 2 m/s. It was observed that high concentration H2 gas was flowing in the middle of the airflow without quick diffusion into the air. A two-dimensional air-H2 -air gas flow model was considered where 100% H2 was flowing in the middle of the airflow, and the gas layers were separated by two fluctuated interfaces. According to the calculation using this model, only limited conditions of the signals can reach to the receiver due to the refraction at the fluctuating air-H2 -air gas interfaces while propagating. It was found that the receiver could hardly detect the signals; hence, the intensity of the signal looked degraded. Graphical abstract: The intensity degradation of ultrasonic signal propagation through two fluctuated interfaces of air-hydrogen two-layer gas flow is due to the refraction at the interfaces.Image 1 Highlights: Ultrasonic signal propagation was studied for two-layer gas flow. Signal intensity was degraded due to refraction at interfaces. Only a part of the signals with specific incident angles can be received. Intensity of signal did not depend simply on the gas concentration.